THE CAPITAL AT GLOBAL-NATIONAL SCALE AND THE UNREST OF NATIONS - Reuben Soto, Sergio (2019)
In this paper, we propose one of the elements that in our opinion explain the growing and widespread manifestations of social unrest among the most diverse peoples of the Earth. The accumulation of capital, as a foundation for the growth of global production, implies limitations for efficient and effective use of scarce resources on the planet. These limitations impose forms of distribution of wealth among peoples resulting in inadequate social production for general needs, creating general social unrest.